Neuroinflammation, autoinflammation, splenomegaly and anemia caused by bi-allelic mutations in IRAK4 - Cooray, Samantha; Price-Kuehne, Fiona; Hong, Ying; Omoyinmi, Ebun; Burleigh, Alice; Gilmour, Kimberly C.; Ahmad, Bilal; Choi, Sangdun; Bahar, Mohammad W.; Torpiano, Paul; Gagunashvili, Andrey; Jensen, Barbara; et al. (Frontiers in Immunology, 2023)
We describe a novel, severe autoinflammatory syndrome characterized by neuroinflammation, systemic autoinflammation, splenomegaly, and anemia (NASA) caused by bi-allelic mutations in IRAK4. IRAK-4 is a serine/threonine kinase with a pivotal role in innate immune signaling from toll-like receptors (TLRs). In humans, bi-allelic mutations in IRAK4 result in IRAK-4 deficiency and increased susceptibility to pyogenic bacterial infections, but autoinflammation has never been described. We describe 5 affected patients from 2 unrelated families with compound heterozygous mutations in IRAK4 (c.C877T (p.Q293*)/c.G958T (p.D320Y) in 2 patients; and c.A86C (p.Q29P)/ c.161+1G>A) resulting in severe systemic autoinflammation, massive splenomegaly and severe transfusion dependent anemia and, in 3/5 cases, severe neuroinflammation and seizures. IRAK-4 protein expression was reduced in peripheral blood mononuclear cells (PBMC), while immunological analysis demonstrated elevated serum tumor necrosis factor (TNF), interleukin (IL) 1 beta (IL-1β), IL-6, IL-8, interferon α2a (IFN-α2a), and interferon β (IFN-β); and elevated cerebrospinal fluid (CSF) IL-6 without elevation of CSF IFN-α despite perturbed interferon gene signature. Mutations were located within the death domain (DD; p.Q29P and the splice site mutation c.161+1G>A) and kinase domain (p.Q293*/p.D320Y) of IRAK-4. Structure-based modelling of the DD mutation p.Q29P showed alteration in the alignment of a loop within the DD with loss of contact distance and hydrogen bond interactions with IRAK-1/2 within the myddosome complex. The impact of the kinase domain mutation p.D320Y predicted a stabilization in the hydrophobic interactions within the kinase active site. Whilst the precise mechanisms of autoinflammation in NASA remain uncertain, we speculate that loss of negative regulation of IRAK-4 and IRAK-1; dysregulation of myddosome assembly and disassembly; or kinase active site instability may drive dysregulated IL-6 and TNF production. Blockade of IL-6 resulted in immediate and complete amelioration of systemic autoinflammation and anemia in all 3 patients treated; however, neuroinflammation has, so far proven recalcitrant to IL-6 blockade and the Janus kinase inhibitor baricitinib, likely due to lack of central nervous system penetration of both drugs. We therefore highlight that bi-allelic mutation in IRAK4 may be associated with a severe and complex autoinflammatory and neuroinflammatory phenotype that we have called NASA, in addition to immune deficiency in humans.